Analysis of the mitochondrial genome of the Camellia sinensis cv. ‘Zhuyeqi’: multichromosomal structure, RNA editing sites, and evolutionary characterization - Chen, Zhiyin; Zhou, Wei; Wang, Zixu; Chen, Ziyi; You, Xinyuan; Gong, Yihui (Frontiers in Plant Science, 2025)
IntroductionTea (Camellia sinensis) is a significant economic crop, and investigations into the structure and function of its mitochondrial genome are crucial for understanding the evolutionary history and genetic characteristics of this species. This study presents the first comprehensive analysis of the mitochondrial genome of the tea cultivar ’Zhuyeqi‘ (Camellia sinensis cv. ‘Zhuyeqi’), aiming to elucidate its genomic structural features, gene composition, and evolutionary patterns. The findings provide a theoretical foundation for genetic breeding and molecular biology research in tea plants.MethodsHigh-throughput sequencing was employed to sequence the mitochondrial genome of ’Zhuyeqi‘. Bioinformatics approaches were utilized for genome assembly and annotation. Various analytical strategies, including identification of RNA editing sites, codon usage bias analysis, repeat sequence recognition, calculation of non-synonymous substitution rates (Ka) and synonymous substitution rates (Ks), comparative genomics, and collinearity analysis, were applied to comprehensively analyze the structural features and evolutionary dynamics of the mitochondrial genome.Results and discussionThe mitochondrial genome of ‘Zhuyeqi’ consists of one circular chromosome and six linear chromosomes, with a total length of 911,255 bp and a GC content of 46%. Genome annotation identified 77 functional genes, including 38 protein-coding genes (PCGs). The study revealed heterogeneously distributed introns within genes such as trnM-CAT (5 copies) and nad1/2/5/7. RNA editing analysis identified 556 C-to-U editing sites, notably enriched in ccmFn (38 sites) and ccmB (34 sites). Codon usage bias analysis indicated that leucine (Leu, 10%) and arginine (Arg, 7%) were the most frequently used amino acids. Repeat sequence analysis showed that dispersed repeats (780, 72%) dominated, with satellite DNA exhibiting significant distribution biases on chr1 (11) and chr3 (5). Ka/Ks analysis revealed that 37 PCGs were under varying selective pressures (0.09–2.70), with rps4 (Pi=0.09) and atp8 (Pi=0.09) showing exceptionally high variability, while rps19 (Pi=0) was completely conserved. Comparative genomics uncovered 66 homologous segments (25,656 bp) between the mitochondrial and chloroplast genomes, containing 27 intact genes such as trnA-UGC, confirming horizontal gene transfer events. Collinearity analysis demonstrated a high degree of conservation in genomic structures between ‘Zhuyeqi’ and closely related Camellia species. This study lays an important theoretical foundation for further elucidating the structural characteristics and evolutionary mechanisms of the tea plant mitochondrial genome.